Sam Sheep can't sleep - Cox, Phil Roxbee; Cartwright, Stephen; Tyler, Jenny (London : Usborne ; Tulsa, Okla. : EDC, 2000)
A story in rhyme about a sheep.
"A phonics reader"--Cover.
Lift-the-flap pages.
1.8.
1.8
1.8
K-3
Keywords: Toy and movable books -- Specimens; Sheep -- Fiction; Stories in rhyme; Toy and movable books; Sheep -- Fiction; Stories in rhyme; Toy and movable books